Changes in the Transcriptome of Dry Leafy Spurge (Euphorbia esula) Seeds Imbibed at a Constant and Alternating Temperature - Foley, Michael E; Chao, Wun S; Doğramaci, Münevver; Horvath, David P; Anderson, James V (Weed science, 2012)
Leafy spurge seeds are responsive to alternating temperature rather than constant temperature for germination. Transcriptome changes of dry leafy spurge seeds and seeds imbibed for 1 and 3 d at 20 C constant (C) and 20 ∶ 30 C alternating (A) temperature were determined by microarray analysis to examine temperature responsiveness. Principal component analysis revealed differences in the transcriptome of imbibed seeds based on the temperature regime. Computational methods in bioinformatics parsed the data into overrepresented AraCyc pathways and gene regulation subnetworks providing biological context to temperature responses. After 1 d of imbibition, the degradation of starch and sucrose leading to anaerobic respiration were common pathways at both temperature regimes. Several overrepresented pathways unique to 1 d A were associated with generation of energy, reducing power, and carbon substrates; several of these pathways remained overrepresented and up-regulated at 3 d A. At 1 d C, pathways for the phytohormones jasmonic acid and brassinosteroids were uniquely overrepresented. There was little similarity in overrepresented pathways at 1 d C between leafy spurge and arabidopsis seeds, indicating species-specific effects upon imbibition of dry seeds. Overrepresented gene subnetworks at 1 d and 3 d at both temperature regimes related to signaling processes and stress responses. A major overrepresented subnetwork unique to 1 d C related to photomorphogenesis via the E3 ubiquitin ligase COP1. At 1 d A, major overrepresented subnetworks involved circadian rhythm via LHY and TOC1 proteins and expression of stress-related genes such as DREB1A, which is subject to circadian regulation. Collectively, substantial differences were observed in the transcriptome of leafy spurge seeds imbibed under conditions that affect the capacity to germinate. Nomenclature: Mouse-ear cress, Arabidopsis thaliana (L.) Heynh.; leafy spurge, Euphorbia esula L. (EPHES).